Strategi Bertutur Media Daring Kompas Selama Masa Pilpres 2019 - Farel Olva Zuve; Refisa Ananda (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
This study aims to explain the strategy of online media speech acts as a medium for providing information to the public, especially in the election process. This needs to be investigated as a form of media views in providing appropriate and appropriate opinions, especially during the election period. One of them is viewed from the editorial in the online media. This study uses a qualitative descriptive method using Brown and Levinson's theory of speech. Data from the utterances in the editorial column of Kompas online media during the 2019 election period. Based on the data found, the key is that the speech strategies used by the online media Kompas, include: a frank strategy without further ado, a frank strategy with positive politeness, and a frank strategy with negative politeness. The speaking strategy that is widely used is the strategy of speaking frankly with positive politeness. The use of frank speaking strategies with positive politeness is used because of the social distance factor between the speaker and the speech partner, which in this case is the editor of the Kompas electronic media, while the speech partner is the reader of the Kompas electronic media.